Pelatihan Penulisan Artikel Kegiatan Pengabdian kepada Masyarakat di STIE Widya Praja Tanah Grogot - Farida Islamiah; Sri Asmirani; Syahrul Syahrul; Isma Muthahharah; Qardawi Hamzah (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2025)
The main issue of this service is the gap between the intensity of Community Service (PkM) implementation and the low publication output of articles in community service journals at STIE Widya Praja Tanah Grogot. The objective of this PkM is to enhance lecturers' technical competence in converting PkM reports into standardized journal manuscripts. The method employed is Participatory Action Research (PAR) through a participatory intensive workshop and coaching clinic model. The results indicate that the intervention was effective, successfully converting four PkM article drafts ready for submission. Socially, the activity triggered a behavioral shift from passive to proactive. Theoretical reflection confirms that the PAR approach, focusing on the Coaching Clinic, is the most efficient strategy for achieving social and academic institutional transformation in regional private higher education institutions.